Scaled-Down Experiments and Numerical Simulations for the Design of a Retention Tank with Rotatable Bucket - Park, Seong Jik; Lee, Chang Gu; Lee, Jemyung; Choi, Won (Journal of Environmental Engineering (United States), 2018)
Retention tanks are constructed to mitigate peak floods and capture sediments by storing combined sewage overflows. A rotatable bucket is used to sweep the settled particles at the bottom of retention tanks. The bucket rotates naturally by the force of gravity when filled with water, and the water drops from the bucket, consequentially cleaning up the sediments that have sunk to the bottom of the retention tank. In this study, a numerical simulation and scaled-down experiments were performed to investigate the influence of the design parameters - bucket height, bucket size, and bottom slope of the retention tank - on cleaning efficiency. The numerical simulation was executed based on a sediment scour model using FLOW-3D commercial software. The sediment scour model was simultaneously combined with a renormalized group (RNG) model to express a viscous and turbulent flow and with a general moving object (GMO) model to describe the bucket rotation. The amount of sediment left on the bottom of the retention tank was strongly dependent on bucket radius and less dependent on bucket height and bottom slope. When the bucket was designed with a height of 5 m, radius of 0.5 m, and bottom slope of 5%, approximately 97% of the sediments were washed out. An experiment using a scaled-down model produced by a three-dimensional (3D) printer based on the law of similarity was also conducted to verify the numerical model's accuracy. The relative error of the total amount of sediments left on the retention tank bottom between the simulation and experiment ranged from 4.6 to 9.7%. A retention tank with rotatable bucket could be used to store overflow water with less energy for maintenance of sediment buildup.
Keywords: FLOW-3D; Retention; Rotatable bucket; Scour model; Threedimensional (3-d); FLOW-3D; Retention; Rotatable bucket; Scaled-down experiment; Sediment scour model; Three-dimensional (3D) printer